The Transfer and Adjustment Problems in the Balkans - Vladimir Gligorov (The Vienna Institute for International Economic Studies (wiiw), 2016)
How to deal with significant external imbalances due to persistent cross-border financial flows which eventually dry out while accumulated foreign debts need to be financed from increased exports? Keynes and Ohlin, primarily, debated an apparently more specific issue of unilateral transfers in the case of German reparations after the World War I and that debate has had lasting influence on the theory of trade and international finance and even on the understanding of the dynamics of exchange rates in financial and fiscal adjustment. These issues have resurfaced in the discussions of financial crisis in a monetary union, like that of the euro area. The aim of this essay is to use the arguments presented in this debate and in subsequent clarifications and extensions to understand the development of external imbalances in the Balkans and the prolonged adjustment in the context of the financial crisis after 2008. The motivation is that this is an important topic in international macroeconomics and a recurrent problem in this region, though I will look more thoroughly only into the last episode of the financial crisis from 2008 onwards. The essay follows the arguments advanced in this classic debate and applies them to examples of post-crisis adjustment in the Balkans (not just in the post-socialist countries, but also looking at the problems that Greece is having with servicing its large foreign debt). The essay should provide the framework for the understanding of Balkan problems of adjustment to outward transfers to service in some cases of unsustainable foreign debts. It also seeks to develop hypotheses that invite a detailed look at the data and their assessment by somewhat more in depth discussion of particular cases.
Keywords: E12; E44; F32; F34; 330; macroeconomic imbalances; current account adjustment; debt problems; Greece; Balkans; Keynes